Bimbingan Kesehatan Mental Pada Majelis Ta'lim Muslimah Masjid Darussalam Kota Wisata Bogor - Liwa Kartina Hapip; Imas Kania Rahman; Nesia Andriana (LP2M IAIN kUDUS, 2022)
Discussion of mental health is an important matter to pay attention to during post-pandemic periode. Majelis ta’lim is one of the forums to guide the mental health of women. This study aims to describe the role of the muslimah majelis ta’lim at the Darussalam mosque, Kota Wisata Bogor, in guiding the mental health of mothers. This study uses a type of descriptive qualitative approach. The findings from the role of Muslimah majelis ta’lim in raising awareness of post-pandemic mental health are; 1. Health education, socialization about perimenopause depression, postpartum depression, Islamic health, 2. Increasing religious understanding which can increase faith and happiness, 3. Discussion related to psychosocial issues regarding parenting and marriage, 4. Workshop on the Qur'an for mothers 5. Empowerment of the poor by providing scholarships and school equipment at the beginning of each academic year, 6. Guiding MSMEs to improve the household economy, 7. Cheer up the poor mothers every year for holidays and increase ukhuwah, 8. Free health checks at the mosque health post every Saturday morning. From the data obtained, it shows that majelis ta’lim carries out maternal mental health guidance activities in various forms of activity.